DLSLA 3D SAR Motion Error Compensation and Imaging Method Based on Parameter Estimation - Liu Qiyong; Zhang Qun; Hong Wen; Su Linghua; Liang Jia (Leida xuebao, 2018)
In the presence of yaw angular velocity, a body will deviate from its ideal flight path, which will affect imaging of Downward-Looking Sparse Linear Array 3D Synthetic Aperture Radar (DLSLA 3D SAR). In this paper, an imaging model including yaw rate is established. Furthermore, Doppler frequency modulation, which is related to cross-track coordinates and not azimuth coordinates, was theoretically calculated. Thus, a cross-track signal could be reconstructed to obtain the cross-track coordinates before azimuth signal compression. Based on the parametric sparse representation, the velocity and yaw rate of the platform were estimated, and the azimuth signal was compressed. Moreover, a deformation correction method is proposed to correct image deformation. The simulation results demonstrate the validity of the proposed method.